Influences of surge motion on the power and thrust characteristics of an offshore floating wind turbine - Wen, Binrong; Tian, Xinliang; Dong, Xingjian; Peng, Zhike; Zhang, Wenming (Energy (Oxford), 2017)
The power and thrust characteristics of an offshore floating wind turbine (OFWT) not only depend on the tip speed ratio λ and the blade pitch angle θ, but also closely relate to the platform motions. In this paper, the influences of the platform surge motion on the behaviors of the power output and rotor thrust of a typical Spar-type OFWT are investigated using Free Vortex Method (FVM). The influences of the surge frequency and amplitude are analyzed separately at first. Afterwards, a reduced frequency k is proposed to combine the influences of surge frequency and amplitude. The power and thrust curves are derived as functions of the tip speed ratio λ and reduced frequency k with blade pitch angle θ constant at zero. Results show that when the reduced frequency increases, mean power output decreases at low tip speed ratios but increases at high tip speed ratios; mean thrust decreases slightly for all tip speed ratios except λ = 12. Power and thrust variations increase as tip speed ratio or reduced frequency increases. Power and thrust coefficients decline with an increasing reduced frequency. •A modification is made to FVM to maintain computational accuracy and reduce cost.•Fluctuation in angle of attack dominates in power and thrust fluctuations.•The reduced frequency k is introduced as an independent variable of power and thrust.•Effect of k on mean power/thrust varies with the tip speed ratio.•As k or tip speed ratio increases, the power and thrust variations increase.